High Dose “HDR-Like” Prostate SBRT: PSA 10-Year Results From a Mature, Multi-Institutional Clinical Trial - Fuller, Donald B.; Crabtree, Tami; Kane, Brent L.; Medbery, Clinton A.; Pfeffer, Robert; Gray, James R.; Peddada, Anuj; Royce, Trevor J.; Chen, Ronald C. (Frontiers in Oncology, 2022)
Purpose/Objective(s): Although ample intermediate-term prostate stereotactic radiotherapy (SBRT) outcomes have been reported, 10-year results remain relatively sparse. Materials/Methods: 18 institutions enrolled 259 low- and intermediate-risk patients. Median follow-up is 5.5 years, with 66 patients followed > 10 years. This SBRT regimen specifically emulated an existing HDR brachytherapy dose schedule and isodose morphology, prescribed to 38 Gy/4 fractions, delivered daily by robotic SBRT, mandating > 150% dose escalation in the peripheral zone. Androgen deprivation therapy was not allowed and hydrogel spacer was not available at that time. Results: Median pre-SBRT PSA of 5.12 ng/mL decreased to 0.1 ng/mL by 3.5 years, with further decrease to a nadir of < 0.1 ng/mL by 7 years, maintained through 10 years. 10-year bRFS measured 100% for low-risk, 84.3% for fav-int risk (FIR) and 68.4% for unfav-int risk (UIR) cases. Multivariate analysis revealed that the UIR group bifurcated into two distinct prognostic subgroups. Those so classified by having Gleason score 4+3 and/or clinical stage T2 (versus T1b/T1c) had a significantly poorer 10 yr. actuarial bRFS rate, 54.8% if either or both factors present, while UIR patients without these specific factors had a 94.4% 10 year bRFS rate. The actuarial incidence of grade 2 GU toxicity modestly increased over time – 16.3% at 5 years increased to 19.2% at 10 years, while the incidence of grade 3+ GU and GI toxicity remained low and stable to 10 years - 2.6% and 0%, respectively. The grade 2 GI toxicity incidence also remained low and stable to 10 years – 4.1 % with no further events after year 5. Conclusion: This HDR-like SBRT regimen prescribing 38 Gy/4 fractions but delivering much higher intraprostatic doses on a daily basis is safe and effective. This treatment achieves a median PSA nadir of <0.1 ng/mL and provides high long-term disease control rates without ADT except for a subgroup of unfavorable intermediate-risk patients.